An Unusual, Intermediate-Sized Lesion Affecting Motor Organization in a Patient With Schizencephaly: A Case Report - Baik, Sung-Woon; Kim, Gi-Wook; Ko, Myoung-Hwan; Seo, Jeoung-Hwan; Won, Yu-Hui; Park, Sung-Hee (Frontiers in Human Neuroscience, 2020)
Schizencephalies are abnormal clefts of the cerebral hemispheres that result from abnormal late neuronal migration and cortical organization. In the present study, we report a different type of unusual motor organization in a patient with a schizencephalic cleft in the right hemisphere and polymicrogyria in the opposite hemisphere. Despite similar brain pathology affecting the sensorimotor cortex, motor organization differed from previously known bilateral congenital brain lesions. We conducted a transcranial magnetic stimulation (TMS) and diffusion tensor image (DTI) study to confirm the motor organization. In this case, ipsilateral corticospinal projections to the paretic hands were observed during TMS of the less affected hemisphere, along with polymicrogyria, similar to the previous study. However, a crossed corticospinal tract to the paretic hand from the more severely affected hemisphere was observed in this case-a pattern of motor organization that has yet to be reported in this patient population. Our findings indicate that motor organization after early brain injury may be affected by the interhemispheric competition of the corticospinal system and bilateral brain lesions, thereby resulting in unilateral hemiparesis.